Learning to be rational in the presence of news: a lab investigation - Lustenhouwer, Joep; Salle, Isabelle (European economic review, 2025)
We conduct a laboratory experiment in a micro-founded macroeconomic model where participants receive public announcements about future government spending shocks, and are tasked with repeatedly forecasting output over a given horizon. By eliciting several-period-ahead predictions, we can investigate forecast revisions in relation to these announcements. We find that subjects learn the magnitude of the effect of the shocks on output, albeit not with perfect accuracy. We find micro-level evidence that they persistently underreact to the announcements in a way consistent with sticky information, but find little support for fully backward-looking expectations. We rationalize the experimental data with a Bayesian updating model, which provides a particularly good description of the behaviors in longer-horizon environments and among attentive, experienced, and effortful subjects.